'An Invasion of Guest Worker Children': Welfare Reform and the Stigmatisation of Family Migration in West Germany. (August 2019) - Stokes, Lauren
Abstract: This article examines the effects of the 1974 child allowance reform on guest worker families in West Germany. As part of a wider reform, West Germany implemented a two-tiered system of child allowances whereby migrant parents received more money for children who lived in the European Economic Community (EEC) than for children who lived outside the EEC. Migrants protested the reform and with it the assumptions of the guest worker programme. However, these parents had to contend with a popular narrative whereby foreign parents who brought their children to West Germany after the reform were in fact irresponsible 'welfare migrants' who placed their desire for financial gain over their children's need for a stable environment. The idea that this specific welfare reform had been the trigger for large-scale family migration not only discouraged further investigation of the causes of family migration but was also used to support new restrictions on that migration.